2007
DOI: 10.1002/ejsp.417
|View full text |Cite
|
Sign up to set email alerts
|

How do i know what i feel? Evidence for the role of self‐categorisation in symptom perceptions

Abstract: This paper extends the self-categorisation model of symptom appraisals to predict that individuals who believe they have a given illness will perceive concurrent symptoms relevant to that illness to be more severe when they categorise themselves as members of a group of people with that illness. These predictions are supported with opportunity samples of individuals reporting, or not reporting a common cold (Study 1, N ¼ 60) and reporting colds or tinnitus (Study 2, N ¼ 64). In both studies, relevant symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…so that asthma informed their sense of social identity) than if they did not. Along similar lines, earlier experimental research by St Claire et al (2008) has also shown that people are far more likely to report symptoms of cold and to request medication when they are primed to think of themselves in terms of a social identity as a cold sufferer.…”
Section: Social Identity Health and Well‐being: An Overview Of Resementioning
confidence: 62%
See 1 more Smart Citation
“…so that asthma informed their sense of social identity) than if they did not. Along similar lines, earlier experimental research by St Claire et al (2008) has also shown that people are far more likely to report symptoms of cold and to request medication when they are primed to think of themselves in terms of a social identity as a cold sufferer.…”
Section: Social Identity Health and Well‐being: An Overview Of Resementioning
confidence: 62%
“…in terms of symptomatology), and if he or she has prior knowledge about the condition (e.g. through health campaigns or previous diagnosis; Adams, Pill, & Jones, 1997; Levine & Reicher, 1996; St Claire, Clift, & Dumbelton, 2008).…”
Section: Understanding the Relationship Between Social Identity And Hmentioning
confidence: 99%
“…First, when people act as group members, then the significance of events is evaluated in relation to the relevant social identity. Notably, where something is construed as either violating the values and norms of the group as a whole or else as threatening the position of an individual as group member, then it will be evaluated negatively (Levine, 1999; Levine & Reicher, 1996; St Claire, Clift, & Dumbelton, 2008). Second, when social identities are salient, people will become more concerned for the fate of fellow group members, and their relations with fellow group members will become more supportive and intimate.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical approach posits that it is this sense of shared social identity, and resultant transformation of social relations, which affect well-being, in part via primary and secondary stress appraisals (Lazarus & Folkman, 1984). From this perspective, experiences of stress are influenced by the values and norms of the group(s) to which one belongs (e.g., Levine & Reicher, 1996;St Claire, Clift, & Dumbelton, 2008). On the other hand, when stress is experienced, the accessibility to social support, afforded by belonging to and identifying with a group, or groups, serves as a resource for coping (e.g., Haslam, O'Brien, Jetten, Vormedal, & Penna, 2005;.…”
mentioning
confidence: 99%